2021
DOI: 10.1039/d0gc03664a
|View full text |Cite
|
Sign up to set email alerts
|

Liquid nanostructure of choline lysinate with water and a model lignin residue

Abstract: The structure of the ionic liquid choline lysinate ([Ch][Lys]) and its water mixtures, including a dissolved model lignin residue, guaiacol, is revealed at atomic and nanoscale resolution using neutron diffraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(43 citation statements)
references
References 35 publications
6
36
0
Order By: Relevance
“…Their superior performance is attributed to their ability to form unique and strong hydrogen bonds with the lignin. 89,90 A more in-depth discussion of specific interactions, and the molecular arrangement of ions will be provided in Section 4.…”
Section: Biomass Processing and Extractionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their superior performance is attributed to their ability to form unique and strong hydrogen bonds with the lignin. 89,90 A more in-depth discussion of specific interactions, and the molecular arrangement of ions will be provided in Section 4.…”
Section: Biomass Processing and Extractionmentioning
confidence: 99%
“…Unlike many conventional ILs, numerous studies have shown that ChAAILs can maintain their high specificity and efficiency as extraction solvents upon water dilution. 28,34,82,86,90 Their high effectiveness at dissolving coal and biomass is attributed to their ability to form strong and extensive H-bonds by the amino acid anion and the solute. 28,90 This is only slightly affected by the addition of water up to 40 wt%.…”
Section: Biomass Processing and Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 However, to date, compared with tremendous experimental and theoretical investigations of imidazolium based IL–water mixtures, 18 only a few reports have focused on the interactions and microstructures of [Cho][AA]–water mixtures. And these studies only involve the single AA − anion (such as glycine, 16 lysine 19 and arginine 17 ), the effect of the AA structure on dynamic interactions between [Cho][AA] and water molecules, and on the resulting microstructures are still blank. Based on the fact that the anion structure of the IL plays a predominant role in its interaction ability and application efficiency, 20 the influences of the side chain length and residue functional group of the AA − anion on interactions and microstructures of [Cho][AA]–water mixtures need to be extensively explored to achieve various applications.…”
Section: Introductionmentioning
confidence: 99%
“…16 It is believed that the macroscopic properties and application efficiencies of IL-water mixtures result from its interaction changes along with water addition. 17 However, to date, compared with tremendous experimental and theoretical investigations of imidazolium based IL-water mixtures, 18 only a few reports have focused on the interactions and microstructures of [Cho][AA]-water mixtures. And these studies only involve the single AA À anion (such as glycine, 16 lysine 19 and arginine 17 ), the effect of the AA structure on dynamic interactions between [Cho][AA] and water molecules, and on the resulting microstructures are still blank.…”
Section: Introductionmentioning
confidence: 99%